Formation of critical and creative thinking in cadets (Eurasian Journal of History, Geography and Economics, 2023)
Creative approaches and achievements have advanced human civilization worldwide in fields ranging from science and technology to philosophy, arts, and humanities (Hennessey and Amabile, 2010 [1]). So, creative thinking is more than just coming up with random ideas.